INDEKS JENTIK DI DAERAH ENDEMIS DAN DAERAH SPORADIS DEMAM BERDARAH DENGUE DI PURWODADI KABUPATEN GROBOGAN - Zumrotus Sholichah; RR. Anggun Paramita Djati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2008)
Dengue Haemorrhagic Fever (DHF) often causes an outbreak, and presently, still no vaccine and drugs are found to overcome this disease. Stratified DHF are devided into four categories namely endemic, sporadic, potential and DHF freedareas. The transmissions of DHF are mostly found in the endemic areas. This study analyzed the data found in Grobogan regency on 2005. The objective of this study is to determine the larvae index (House Index, Container Index, Breteau Index) both in endemic area and sporadic area, by using an independent t-test. Result of the study showed that some parameters of larvae index in the endemic areas were described as HI = I9,96%, CI = I4,I4% and BI = 2I,86%. Yet, it appeared to have adifferent resut sporadic area (HI= 19,3 3%; CI = I 3, 2 7%; and BI= 26, 99%).